BEARINGLESS ROTOR SYSTEM MAIN COMPONENTS DESIGNING - Zhosan, Oleksandr (Problems of Friction and Wear, 2024)
Bearingless rotor system design optimizes mechanical simplicity, eliminates frictional losses typical of conventional bearing systems, and improves the overall efficiency of the rotor system. Based on the findings of the research, it is possible to determine that composite materials can be applied in order to improve the performance of the rotorcraft rotor system.A theoretical analysis of the influence of input parameters on the aerodynamic quality of the main rotor of a rotorcraft was carried out. The strength and aerodynamic quality of the designed parts were calculated using the finite element analysis method. The energy efficiency of the use of composite materials is substantiated, which will ensure better efficiency and competitiveness of the aircraft.